Evaluation of the addition of ascorbic acid to the ration of cultivated Piaractus mesopotamicus (Characidae) on the infrapopulation of Anacanthorus penilabiatus (Monogenea) - Martins, M.L. [UNESP] (Associação Brasileira de Divulgação Científica (ABRADIC), 1998)
Sixty Piaractus mesopotamicus Holmberg, 1887 (pacu) fry fed a diet containing 0, 50, 100 and 200 mg ascorbic acid/kg dry feed were studied to evaluate the effect on parasitic infestation by the monogenean Anacanthorus penilabiatus Boeger, Husak and Martins, 1995 (Monogenea: Dactylogyridae) for a period of 24 weeks. The temperature of the aquaria was measured daily and remained between 28 and 31oC. At the beginning of the experiment, fish showed 6.15 ± 0.33 cm standard length and 8.64 ± 1.62 g average body weight. A sample of fish was examined and showed 43 ± 17 monogeneans per fish. At the end of the experiment, the gills of control and vitamin C-treated fish were collected for parasite counts. Control fish had 42.5 parasites per fish, a significantly higher number (P<0.05) when compared with fish fed vitamin C, that showed 16.5 parasites per fish. Ascorbic acid fortification in the food promoted an increase in fish resistance to parasites. It is suggested that an optimum level of 139 mg/kg vitamin C supplementation either elicited better nutritional conditions by stimulating the appetite of the fish or improved the immune response.
Keywords: ascorbic acid; monogenean; Anacanthorus penilabiatus; infestation; fish; Piaractus mesopotamicus